Antispasmodic Effect of Alstonia boonei De Wild. and Its Constituents: Ex Vivo and In Silico Approaches - Opeyemi Josephine Akinmurele; Mubo Adeola Sonibare; Anthony A. Elujoba; Akingbolabo Daniel Ogunlakin; Oloruntoba Emmanuel Yeye; Gideon Ampoma Gyebi; Oluwafemi Adeleke Ojo; Abdullah R. Alanzi (Molecules, 2023)
Background: Alstonia boonei, belonging to the family Apocynaceae, is one of the best-known medicinal plants in Africa and Asia. Stem back preparations are traditionally used as muscle relaxants. This study investigated the antispasmodic properties of Alstonia boonei Stem back and its constituents. Method: The freeze-dried aqueous Stem back extract of A. boonei, as well as dichloromethane (DCM), ethyl acetate, and aqueous fractions, were evaluated for their antispasmodic effect via the ex vivo method. Two compounds were isolated from the DCM fraction using chromatographic techniques, and their antispasmodic activity was evaluated. An in silico study was conducted by evaluating the interaction of isolated compounds with human PPARgamma-LBD and human carbonic anhydrase isozyme. Results: The Stem back crude extract, DCM, ethyl acetate, and aqueous fractions showed antispasmodic activity on high-potassium-induced (K+ 80 mM) contractions on isolated rat ileum with IC50 values of 0.03 ± 0.20, 0.02 ± 0.05, 0.03 ± 0.14, and 0.90 ± 0.06 mg/mL, respectively. The isolated compounds from the DCM fraction were β-amyrin and boonein, with only boonein exhibiting antispasmodic activity on both high-potassium-induced (IC50 = 0.09 ± 0.01 µg/mL) and spontaneous (0.29 ± 0.05 µg/mL) contractions. However, β-amyrin had a stronger interaction with the two proteins during the simulation. Conclusion: The isolated compounds boonein and β-amyrin could serve as starting materials for the development of antispasmodic drugs.